2015
DOI: 10.1111/japp.12160
|View full text |Cite
|
Sign up to set email alerts
|

Scepticism about Beneficiary Pays: A Critique

Abstract: Some moral theorists argue that being an innocent beneficiary of significant harms inflicted by others may be sufficient to ground special duties to address the hardships suffered by the victims, at least when it is impossible to extract compensation from those who perpetrated the harm. This idea has been applied to climate change in the form of the beneficiary‐pays principle. Other philosophers, however, are quite sceptical about beneficiary pays (both in general and in the particular case of human‐induced cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 6 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…An alternative approach is the so-called Beneficiary Pays Principle [16,40,51,60,63,64] (p. 536). Although previous generations may have passed away, present generations still reap the benefits of past industrial activities involving the burning of fossil fuels.…”
Section: Left-libertarianism: Carbon Budget and Historical Responsibilitymentioning
confidence: 99%
“…An alternative approach is the so-called Beneficiary Pays Principle [16,40,51,60,63,64] (p. 536). Although previous generations may have passed away, present generations still reap the benefits of past industrial activities involving the burning of fossil fuels.…”
Section: Left-libertarianism: Carbon Budget and Historical Responsibilitymentioning
confidence: 99%
“…In response to these objections, some authors have argued in favor of the beneficiary pays principle (BPP), according to which "the countries benefiting the most from greenhouse emitting activities in the past bear the greatest responsibility of climate justice" (Page 2008, p. 562; see also Barry and Kirby 2017;Duus-Otterström 2017). 3 In one interpretation, the BPP is constructed around the legal doctrine of unjust enrichment (Page 2012;Heyd 2017).…”
Section: Introductionmentioning
confidence: 99%
“…What is crucial is whether in Benefitting from Terrorism, one would feel morally bound to offer apology, 27 An implication of the non-identity problem is that in many cases, current people can't be said to be benefitting from past injustices if these injustices are also conditions for their existence, as there is no alternative world in which they exist but don't benefit (Caney 2006). Some have suggested that the BPP isn't entirely vulnerable to that objection as it could merely limit its application (Barry and Kirby 2017). Others have suggested possible ways of avoiding the problem altogether (Butt 2007).…”
Section: The Normative Connection Argument For the Beneficiary Pays Pmentioning
confidence: 99%